A Game Theory-Based Approach to Hierarchically Rank Responses to Geological and Geotechnical Risks - Mohammad Amin Ghasvareh; Gholam Reza Lashkaripour; Hossein Sadeghi; Javad Tayyebi (مجله مدل سازی در مهندسی)
Due to uncertainty in design, financial estimates, geotechnical and geological issues, tunneling projects are always associated with risks. The project's functional goals may be lost or even fail if these risks are not managed. Many tunnel construction projects have experienced failures that have caused a lot of damage. The use of risk management knowledge is necessary to achieve the main goals in tunnel project construction. One of the most significant challenges for engineers is identifying and assessing risks in tunneling projects, which can lead to proper risk management during tunnel construction. A game theory-based method has been developed to study the risks in tunnel construction projects in this research. To verify the proposed model, as an experimental study, the existing geological and geotechnical risks on line 3 of the Mashhad urban Subway were investigated. Based on the degree of importance, the responses to the desired risks are determined and prioritized in the following. The results showed that preparing engineering geological profiles along the route using the obtained information and changing the excavation parameters based on it with soil Improvement methods are the most significant risk response.